Transabdominal ultrasonography – A tool for optimising reproductive management of sheep - Maurya, V P; Sejian, V; Naqvi, S M K (Indian Farming, 2015)
The early and precise detection of pregnancy in sheep is especially important from an economical point of view. The separation of flocks into pregnant and non-pregnant permits a scheduling of the technology of breeding, reduction of reproductive diseases and optimization of the live weight of mothers and neonates. Non-pregnant ewes may be rebred or could be sold, reducing feed expenses. Determining the number of fetuses at early stage of gestation allows for planning the technological regimen of feeding and breeding, herd replacement, and to protect the sheep from toxemia in the late stage of pregnancy. In addition, the accurate information on the stage of gestation would be useful to dry off lactating females at adequate period and to monitor the females near term. One of the greatest advantages of ultrsonography is that it is totally non-invasive and so repeated examinations of an animal’s reproductive tract can be performed without impairing its breeding potential or having adverse effect on the conceptus. Development of new integrated reproductive management systems with combination of ultrasonography will further enhance the practical utility of ultrasonography and will help in increasing in sheep production.